IS PSYCAP THE DETERMINANT FACTOR FOR WORK ENGAGEMENT AMONG EMPLOYEES OF PRIVATE INSURANCE SECTOR - D Avadhani, Vidya; B Menon, Rethy (International Journal of Psychosocial Rehabilitation, 2020)
PsyCap(Psychological Capital) is the positive psychological state of a human being for development. This topic has taken prominence in various fields since it is a basic psychological need for an individual for the better survival. Individuals with high level of PsyCap are positively motivated towards their work and their satisfaction level is also high. The current study focused on finding out the level of PsyCap and employee engagement as well as relationship linking PsyCap on employee engagement among employees of Private Insurance sectors. Structured questionnaires on PsyCap and employee engagement is administered for data collection and data is collected from 100 employees of private insurance sector. Descriptive statistics, t test and correlation is used for analysing the data. The finding found out that the employees PsyCap is moderate level and employee engagement is also at low level and there exists high correlation between PsyCap and employee engagement among the employees of private insurance sector.